2010
DOI: 10.1111/j.1468-5884.2010.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Is learning a family matter?: Experimental study of the influence of social environment on learning by older adults in the use of mobile phones

Abstract: It is necessary to investigate the ways in which designs for the use of artifacts created by information technology (IT) can improve the quality of life of older adults who use these devices. The present research investigated how older adults learned to use mobile phones in daily life; it focused on the effects that families may exert on the acquisition of this kind of knowledge. A 3-week experiment was conducted with 11 users who had no previous experience using mobile phones. For half of the participants, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Dai, Chen, and Rau (2012) who examined the application of mobile learning in Collaborative Problem-based Learning environments, indicated that the effects of problem-based learning pedagogies were mostly positive, therefore strengthened the teachers' confidence for further application of it to the rest of his courses. Mori and Harada (2010) suggest that differences in users' social environments create differences in the levels of use of mobile learning. Lam, Yau, and Cheung (2010) found that m-learning provided the possibility of improving interaction and collaboration among students and teachers.…”
Section: Theory and Research Backgroundmentioning
confidence: 98%
“…Dai, Chen, and Rau (2012) who examined the application of mobile learning in Collaborative Problem-based Learning environments, indicated that the effects of problem-based learning pedagogies were mostly positive, therefore strengthened the teachers' confidence for further application of it to the rest of his courses. Mori and Harada (2010) suggest that differences in users' social environments create differences in the levels of use of mobile learning. Lam, Yau, and Cheung (2010) found that m-learning provided the possibility of improving interaction and collaboration among students and teachers.…”
Section: Theory and Research Backgroundmentioning
confidence: 98%
“…Smith (2014), for example, reported that only 18% of older adults ''would feel comfortable learning to use a new technology device such as a smartphone or tablet on their own,'' while 77% indicate ''they would need someone to help walk them through the process.'' Older adults rely heavily on social networks and/or social support in order to acquire ICT-related skills, which are also needed for the use of mobile phones (Mori and Harada, 2010). Besides studying the structure of social support networks and household size, it is suggested that the family structure (e.g., three-generation households and husband-and-wife-only households) should also be included in the study of the learning and adopting process of mobile phones among older adults.…”
Section: Findings and Theoretical Considerationsmentioning
confidence: 99%
“…Mobile devices can help parents to monitor how their children perform in a learning environment [9]. The use of technology may differ depending on the user's environment [61]. The use of mobile learning encourages students to learn alone without an instructor's help but meanwhile enhancing the interaction between them [26].…”
Section: Previous Studies In M-learningmentioning
confidence: 99%